Irrigação e fertirrigação em um sistema de aspersão convencional submetido à técnicas de controle estatístico de qualidade. - Justi, André Luiz (2008)
The contribution of irrigation in the alimentary supply, is due to the fact of more and more to look for more efficient systems, monitoring the indexes of uniformity of distribution of the water. The application of fertilizers through irrigation water took very big pulse in the last times, mainly due to the emergence of pressurized systems, of the tunnels of plastic, of the increment of the located irrigation and of the researches proving that the application of liquid fertilizers becomes more appropriate to the plants, to the soil and, besides under the analysis of the involved economical aspects. Being necessary tests to verify the system this operating appropriately in field in order to avoid losses so much in productivity as maintenance of systems. It was aimed at with this work to evaluate an overhead irrigation for aspersion, so much in the application of water as in the fertilizer application, and to submit him/it to quality control techniques to evaluate the capacity of the process. The experiment was driven in the Experimental Nucleus of Engineering Agricultural, belonging the State University of the West of Paraná, located in the km 95 of the highway BR 467. They were appraised 25 irrigations and 25 fertigations, following the established methodology for NBR 7749 (ABNT, 1999). For the irrigation, they were obtained values of Coefficient of Uniformity of Christiansen (CUC) of 72,25 and 89,45% as values minimum and maximum, and a medium CUC of 79,72%, considered value below the minimum of 80% for irrigation for aspersion, and the system operated in wind conditions with speeds of up to 2,97 m.s-1. For fertigation, the values of found CUC were 70,91 and 81,04% as minimum and maximum, and a medium CUC of 77,14%, under maximum wind of 2,18 m.s-1.Aplicando the quality control tests, for the irrigation with water, it was obtained a correlation index between CUC and the speed of the wind of 83,6% and 68,4% for the irrigation and fertigation, respectively and a correlation among CUC and to the index of capacity of process (CP) of 63,3 and 20,9% for the irrigation and fertigation, respectively.